SPSS for intermediate statistics : use and interpretation - 249671 Leech, Nancy L.; Barrett, Karen Caplovitz; Morgan, George A. (George Arthur), 1936- (Mahwah, NJ : Lawrence Erlbaum Associates, 2005)
36